In Defence of Country: Life Stories of Aboriginal and Torres Strait Islander Servicemen and Women - Riseman, Noah (ANU Press, 2016)
Aboriginal and Torres Strait Islander people have been protecting country since time immemorial. One way they have continued these traditions in recent times is through service in the Australian military, both overseas and within Australia. In Defence of Country presents a selection of life stories of Aboriginal and Torres Strait Islander ex-servicemen and women who served in the Australian Army, Navy and Air Force after World War Two. In their own words, participants discuss a range of issues including why they joined up; racial discrimination; the Stolen Generations; leadership; discipline; family; war and peace; education and skills development; community advocacy; and their hopes for the future of Indigenous Australia. Individually and collectively, the life stories in this book highlight the many contributions that Aboriginal and Torres Strait Islander servicemen and women have made, and continue to make, in defence of country.